How to make product development projects more successful by integrating Kano's model of customer satisfaction into quality function development - Matzler, Kurt (Technovation)
Managers are offered step by step tools and methods for ensuring greater success in product development based on integrating Kano's model of customer satisfaction into quality function deployment. A case based on the ski industry is used as an illustration